PENGARUH SUHU DAN WAKTU REAKSI TRANSESTERIFIKASI MINYAK BIJI BUNGA MATAHARI TERHADAP METIL ESTER DENGAN KATALIS NaOH - Aulia, Muhammad Rifki; Azhari, Azhari; Meriatna, Meriatna; Ginting, Zainuddin; Sylvia, Novi (Chemical Engineering Journal Storage (CEJS), 2022)
The rapid development of technology and science has made vegetable oil not only as a consumption material, but also into something more useful, namely alternative renewable fuel oil, one of which is biodiesel which is an alternative fuel to replace diesel. The purpose of this study was to examine the effect of temperature and time of the transesterification reaction on the characteristics of the biodiesel produced. The expected results are results that are in accordance with the characteristics of biodiesel with SNI parameters. This research was conducted by mixing sunflower seed oil with methanol as a solvent with a NaOH catalyst with a mole ratio of reactants 1:6. Then the variation of reaction time was determined, namely 70 minutes, 80 minutes and 90 minutes, and the reaction temperature was 50°C, 55°C, 60°C and 65°C, respectively. After biodiesel is obtained, characteristic testing is carried out. The results showed that the best biodiesel quality was obtained at a temperature of 60°C with a reaction time of 90 minutes with the following characteristics: Yield = 80.76%; density = 0.85 gr/ml; viscosity = 2.38 cSt; water content = 0.03 %vol and acid number = 0.5 mg-KOH/g. Thus, it can be concluded that the biodiesel produced is in accordance with the characteristics of the standardization parameters of SNI-7182-2019 regarding biodiesel.